2021
DOI: 10.1186/s12917-021-02829-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of β-catenin, Ki67, CD3 and CD18 in canine colorectal adenomas and adenocarcinomas

Abstract: Background Inflammation is believed to influence human colorectal carcinogenesis and may have an impact on prognosis and survival. The mucosal immunophenotype in dogs with colorectal cancer is poorly described. The aim of this study was to investigate whether the density, distribution and grade of tumor-infiltrating immune cells (TIIs) are different in normal colonic tissue vs benign stages (adenomas) and malignant stages (adenocarcinomas) of canine colorectal carcinogenesis, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…From a comparative point of view, in intestinal neoplasms in dogs, CTNNB1 mutations were proven to be more often causative than APC mutations, with CTNNB1 being mutated in >60% of canine colorectal tumors [ 22 ]. Several studies also provide evidence of nuclear β-catenin translocation and accumulation in canine intestinal adenomas and carcinomas [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a comparative point of view, in intestinal neoplasms in dogs, CTNNB1 mutations were proven to be more often causative than APC mutations, with CTNNB1 being mutated in >60% of canine colorectal tumors [ 22 ]. Several studies also provide evidence of nuclear β-catenin translocation and accumulation in canine intestinal adenomas and carcinomas [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors suggest this may be due in part to the unique properties of bone, namely that cytokines responsible for M2 differentiation can also inhibit osteoclast formation ( 170 ). In canine colorectal cancer, one study found no significant difference in macrophage counts between control tissue, adenomas, and carcinomas, while another found lower levels of macrophages in adenomas and carcinomas as compared to controls ( 144 , 145 ).…”
Section: Tams In Companion Dogsmentioning
confidence: 96%
“…IHC was conducted using antibodies against rabbit polyclonal Ki-67 (ab15580; Abcam, Waltham, MA, USA), previously used in canine tissues [15,16]. After deparaffinizing and rehydration with xylene and alcohol, slides were washed under tap water for 10 min.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%